Epilepsy Disease and Nose-to-Brain Delivery of Polymeric Nanoparticles: An Overview - Teresa Musumeci; Angela Bonaccorso; Giovanni Puglisi (MDPI AG, 2019)
Epilepsy is the fourth most common global neurological problem, which can be considered a spectrum disorder because of its various causes, seizure types, its ability to vary in severity and the impact from person to person, as well as its range of co-existing conditions. The approaches to drug therapy of epilepsy are directed at the control of symptoms by chronic administration of antiepileptic drugs (AEDs). These AEDs are administered orally or intravenously but alternative routes of administration are needed to overcome some important limits. Intranasal (IN) administration represents an attractive route because it is possible to reach the brain bypassing the blood brain barrier while the drug avoids first-pass metabolism. It is possible to obtain an increase in patient compliance for the easy and non-invasive route of administration. This route, however, has some drawbacks such as mucociliary clearance and the small volume that can be administered, in fact, only drugs that are efficacious at low doses can be considered. The drug also needs excellent aqueous solubility or must be able to be formulated using solubilizing agents. The use of nanomedicine formulations able to encapsulate active molecules represents a good strategy to overcome several limitations of this route and of conventional drugs. The aim of this review is to discuss the innovative application of nanomedicine for epilepsy treatment using nose-to-brain delivery with particular attention focused on polymeric nanoparticles to load drugs.